The Effects of Sulphaquinoxalin in Broiler Chicken: Clinical Symptom and Anatomical Pathology - M. Nur Salim; Dian Masyitha (Jurnal Kedokteran Hewan, 2010)
The clinical symptom and anatomical pathology effect of sulphaquinoxalin administration were studied in 12 male -seven days-old Hubbard broiler chickens with the weight of 85.57.83 g. The chickens were randomly dividedinto 2 groups of 6 each. The P0 group as control group just orally received aquadest and the P groups were treated 1 orally with 0.1% sulphaquinoxalin which dissolved in drinking water. The sulphaquinoxalin was administrated forseven days. At the end of experiment all chickens were sacrificed for necropsy. The results indicated that less appetite and drinking water as well as decrease of body weight (P0.01). Ptechial haemorrhagic was seen in thorax andfemur muscle, mucosa of duodenum, liver, kidney, heart, lung, and spleen. The liver, kidney, heart, and spleen were swollen.